Multiplicative inequalities in regions with noncompact boundary - Tedeev , A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Exact embedding theorems of the multiplicative type are established for functions of Sobolev spaces defined in a domain Ω ⸦ Rn, п ≥ 2, whose boundary is not compact. The main condition on the domain is of the isoperimetric type.